2018
DOI: 10.4196/kjpp.2018.22.4.419
|View full text |Cite
|
Sign up to set email alerts
|

The effect of µ-opioid receptor activation on GABAergic neurons in the spinal dorsal horn

Abstract: The superficial dorsal horn of the spinal cord plays an important role in pain transmission and opioid activity. Several studies have demonstrated that opioids modulate pain transmission, and the activation of µ-opioid receptors (MORs) by opioids contributes to analgesic effects in the spinal cord. However, the effect of the activation of MORs on GABAergic interneurons and the contribution to the analgesic effect are much less clear. In this study, using transgenic mice, which allow the identification of GABAe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… 66 The application of DAMGO led to the presynaptic inhibition of primary afferent neurons and decreased the frequencies of mEPSCs via the activation of presynaptic MORs. 4 , 66 , 67 MORs also serve as the crucial role in postsynaptic transmission, as bath application of DAMGO induces an directly outward current mediated by activation of K + channels and reduces the amplitude of EPSCs of GABAergic interneurons which might receive monosynaptic inputs from primary nociceptive C fibers, and the downregulation of MORs could weaken the inhibition of postsynaptic neurons excitability, which could be explained by hypersensitivity in pain states. 66 , 67 Indeed, our data showed that IL‐10 and β‐endorphin inhibited excitatory transmission mediated by presynaptic and postsynaptic MORs in spinal cord, and using double immunohistochemical staining, MORs were significantly colocalized with bassoon and NeuN in laminae I/II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 66 The application of DAMGO led to the presynaptic inhibition of primary afferent neurons and decreased the frequencies of mEPSCs via the activation of presynaptic MORs. 4 , 66 , 67 MORs also serve as the crucial role in postsynaptic transmission, as bath application of DAMGO induces an directly outward current mediated by activation of K + channels and reduces the amplitude of EPSCs of GABAergic interneurons which might receive monosynaptic inputs from primary nociceptive C fibers, and the downregulation of MORs could weaken the inhibition of postsynaptic neurons excitability, which could be explained by hypersensitivity in pain states. 66 , 67 Indeed, our data showed that IL‐10 and β‐endorphin inhibited excitatory transmission mediated by presynaptic and postsynaptic MORs in spinal cord, and using double immunohistochemical staining, MORs were significantly colocalized with bassoon and NeuN in laminae I/II.…”
Section: Discussionmentioning
confidence: 99%
“…4,66,67 MORs also serve as the crucial role in postsynaptic transmission, as bath application of DAMGO induces an directly outward current mediated by activation of K + channels and reduces the amplitude of EPSCs of GABAergic interneurons which might receive monosynaptic inputs from primary nociceptive C fibers, and the downregulation of MORs could weaken the inhibition of postsynaptic neurons excitability, which could be explained by hypersensitivity in pain states. 66,67 Indeed, our data showed that IL-10 and β-endorphin Disinhibition of inhibitory transmission closely related from descending inhibitory system were also arisen and also implicated the trans-synaptic effects induced by enhanced excitatory transmission. In behavioral tests, no matter the drugs applied, mechanical thresholds of neuropathic rats could not totally reverse, it might be inferred that those impairments induced neuronal organization and synaptic arrangements might be implicated in the behavioral observations.…”
Section: Discussionmentioning
confidence: 99%
“…Under our recording conditions, DAMGO, deltorphin‐II and U69593 induced outward currents in some SDH target neurons (Figs 6– and 8). These outward currents, probably opioid‐induced potassium channel currents, were reversed by CTAP, ICI174864 and nor‐BNI, respectively (Figs 6– and 8) (Eckert & Light, 2002; Kim et al., 2018; Santos et al., 2004; Wang et al., 2018). Postsynaptic currents in response to DAMGO (62.5 ± 60.8 pA, n = 33/56 neurons) and deltorphin II (18.2 ± 12.5 pA, n = 10/26 neurons) were commonly detected, while small U69593 stimulated currents were measured in a minority of SDH neurons (10.5 ± 3.4 pA, n = 9/49 neurons; Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Intrathecal injection of mu (μ), kappa (κ) and delta (δ) opioid receptor agonists (Bailey et al., 1993; Borgbjerg et al., 1996; Goodchild & Gent, 1992; Morgan et al., 1992; Schmauss, 1987) is generally analgesic, although the data for κ‐agonists are somewhat inconsistent (Danzebrink et al., 1995; Kim et al., 2011). Within the SDH, opioid receptor activation inhibits excitatory synaptic currents (EPSCs), particularly those originating from primary sensory afferents (Gerhold et al., 2015; Glaum et al., 1994; Hori et al., 1992; Kim et al., 2018; Kohno et al., 1999; Randic et al., 1995; Snyder et al., 2018). In contrast, opioid modulation of inhibitory synaptic currents (IPSCs) has not been reliably observed (Grudt & Henderson, 1998; Kerchner & Zhuo, 2002; Kohno et al., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…31 Prolonged iatrogenic activation µ-opioid receptors in the spinal cord suppresses inhibitory GABAergic interneurons and can heighten pain transmission through the superficial dorsal horn pathways. 32 Together, these mechanisms can lead to sustained perception of pain beyond expected tissue recovery.…”
Section: Discussionmentioning
confidence: 99%